Features of the Lithuanian Partisan Underground State - Petrauskienė, Aistė (Tautosakos darbai, 2017)
The great attention that history of the partisan war received in the course of the first decade of the Lithuanian independence has afterwards gradually diminished. It was somewhat revived during the last several years due to the current geopolitical developments in Eastern Europe, however, no new interpretations of the history of partisan war emerged. This article suggests a new approach to the partisan war, which gives priority to the primary sources and rests on the theoretical model of the underground state developed by historian Dawid Fajnhauz. Reconstruction of the Lithuanian partisan underground state presents a new interpretation of partisan war based on an entirety of four source groups (partisan documentation, oral history, things, and places); military documents by Lithuanian partisans receive priority over the Soviet ones. Theoretical reconstruction of the underground partisan state rests on all the features characteristic to its definition. The partisan government, legal acts, armed forces, control of the territory in the present and future time and many other important phenomena legitimize the research hypothesis of the partisan state. This legitimization is also related to the social environment of the interwar independent Lithuania and political attitude based on democratic principles. The idea of the partisan state aims at introducing the Lithuanian partisan war as an example of a modern democratic state, as well as marking guidelines for broader historical research, liberating this research from the trap set by the powerful Soviet propaganda and finally making the history of the partisan war our own. Although the concept of the partisan state can hardly be expected to change the consciousness of people having some sort of related personal experience, or to alter rigid attitude of the academic community, this narrative is primarily directed at the new generation that is still shaping its knowledge of history. This promotes and establishes a notion that freedom fighters resisting the Soviet occupation created an underground state, which embodied the wish of the majority of Lithuanian citizens to live in an independent and democratic country, as testified by the results of the referendum that took place on February 9, 1991.